Time reversal focusing in the audible range using a tunable sonic crystal - Gomez, Valeria Sol (2021)
Time reversal (TR) focusing of acoustical waves is a widely studied phenomenon that usually requires a chaotic cavity or disordered scattering medium to achieve spatial and frequency decorrelation of the acoustic field when using a single channel. On the other hand, sonic crystals were disregarded as scattering media for the TR process because of their periodic structure and previous results showing poor spatial focusing when compared to a disordered medium. In this paper, an experimental realization of a tunable sonic crystal, which can achieve single-channel TR focusing amplitudes in the audible range comparable to those obtained in a disordered scattering medium, is presented. Furthermore, the tunable nature of the system allows it to switch the time-reversed pulse on and off by changing its geometrical configuration. A robustness analysis with respect to the perturbations in the sonic crystal configurations is also presented, showing that the time-reversed pulses with high temporal and spatial contrasts are preserved only for configurations that are close to the original one.